Factors Related To Work Fatigue: Literature Review - Permatasari, Widya (Universitas Pembangunan Nasional Veteran Jakarta, 2020)
Background: Fatigue is one of the problems in the field of Occupational Safety and Health (K3) that able to cause occupational accidents. Work fatigue is a complex problem related to decreased work skills, work enthusiasm, and work productivity. According to BPJS Ketenagakerjaan in 2019 reagarding workplace acids, the tired worker is at more serious risk experience work accidents, 16% reported at least experience a work accident due to fatigue.The purpose of this study is to analyze the factors related to work fatigue and to analyze the factors that are most influential to work fatigue. Methods: The method used in this study is literature review. Result: The results of scientific articles showed that there were 25 studies used in 2010 until 2020. Most of the research designs used cross sectional. There are 12 factors related to the occurrence of work fatigue including age, nutritional status, gender, working period, noise, working climate, lighting, workload, length of work, rest time, work shift and work stress. Conclusion: The workload is the most influential factor with the occurrence of work fatigue.Keywords: Work Fatigue, Factors, Determinants